MATERIAL MANAGEMENT SYSTEM ON NARROW LAND IN THE TOTAL REHAB PROJECT OF THE NEW PEMURUS HEALTH CENTER - Muhammad Ferdy Perdana Muchlis; Retna Hapsari Kartadipura; Abdul Karim (CERUCUK, 2023)
Several methods are commonly used to overcome material management system problems in projects, these methods include the material selection stage, supplier selection, material purchase stage, material delivery stage, material acceptance stage, material storage stage, material production stage, and material inventory level. Before entering the material management system, you must determine what materials are entered into the system, one of which uses Pareto analysis. Pareto diagrams are a standard method of quality control to get the most out of it or choose the main problems and after all are considered as a simple approach that can be understood by less-educated workers, as well as as a tool for solving in a fairly complex field. From the results of Pareto analysis calculations, it is known that the types of materials included in the material management system are Reinforced Iron, Formwork, and Ready Mix. Good material management, it will make it easier to handle work based on procedures that have been arranged systematically. With a clear and systematic management format, it will be able to minimize the occurrence of things that will cause losses on the part of the company. Keywords: Pareto Analysis, Management System, Materials.